Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s10661-017-5821-x
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of spatial distribution of soil heavy metals using ANN-GA, MSLR and satellite imagery

Abstract: This study aims to assess and compare heavy metal distribution models developed using stepwise multiple linear regression (MSLR) and neural network-genetic algorithm model (ANN-GA) based on satellite imagery. The source identification of heavy metals was also explored using local Moran index. Soil samples (n = 300) were collected based on a grid and pH, organic matter, clay, iron oxide contents cadmium (Cd), lead (Pb) and zinc (Zn) concentrations were determined for each sample. Visible/near-infrared reflectan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Cadmium is the seventh most toxic heavy metal as per the agency for toxic substances and disease registry (ATSDR) ranking and also low level permissible exposure to humans (Kabata-Pendias, 2010). It has various anthropogenic sources of exposure like industrial activities and transportation, and natural factors like wind, topography and streams that distribute Cd (II) into the environment (Nadari et al, 2017). In trace quantities, Cd (II) has many hazardous effects on plants by disordering their metabolisms cycles (Shi et al, 2010;Nazar et al, 2012) and cause of many human diseases like digestive system, respiratory system, acute intoxication, kidney damage, bone damage and carcinogenicity (Godt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is the seventh most toxic heavy metal as per the agency for toxic substances and disease registry (ATSDR) ranking and also low level permissible exposure to humans (Kabata-Pendias, 2010). It has various anthropogenic sources of exposure like industrial activities and transportation, and natural factors like wind, topography and streams that distribute Cd (II) into the environment (Nadari et al, 2017). In trace quantities, Cd (II) has many hazardous effects on plants by disordering their metabolisms cycles (Shi et al, 2010;Nazar et al, 2012) and cause of many human diseases like digestive system, respiratory system, acute intoxication, kidney damage, bone damage and carcinogenicity (Godt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among modeling approaches, ANN has been widely used to estimate some soil properties including Cd [31][32][33]. In a recent conference, Ghazi [31] presented an approach in which a neural network is used to estimate the concentrations of Cd with variables such as soil retention, release reactions of solutes, and the soil matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, although few, have been conducted to address the most complicated but important task of estimating spatial and temporal concentrations of Cd. For example, an ANN-GA model (artificial neural network-genetic algorithm), which has been proven to have better performance than ANN alone, was developed by Nadri et al to estimate Cd removal and determine heavy metal contamination [32]. However, due to the black-box property of this method, many networks developed from this algorithm lack ecological, biological, geological, and topological principles.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between the pixel values of satellites imaginary and analyzed parameters in soil and water is continuously being monitored for the development of suitable predication model. Nadari et al [43] reported that the assessment and predication of heavy metals around the contaminated sites using stepwise multiple linear regression and neural network-genetic algorithm model based on visible/near-infrared reflectance of electromagnetic range of satellite imagery provides reliable information. Thus, relation between satellite spectral response and elemental concentration in soil is needed to be study.…”
Section: Introductionmentioning
confidence: 99%